2014
DOI: 10.1016/j.jpowsour.2014.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Thermal parameters determination of battery cells by local heat flux measurements

Abstract: A new approach to the determination of the thermal parameters of high-power batteries is introduced here. Application of local heat flux measurement with a gradient heat flux sensor (GHFS) allows determination of the cell thermal parameters in different surface points of the cell. The suggested methodology is not cell destructive as it does not require deep discharge of the cell or application of any charge/discharge cycles during measurements of the thermal parameters of the cell. The complete procedure is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…The conventional thermal characterization procedure was compared with the experimental results. It was concluded that errors for the thermal conductivity and the specific heat capacity were 0.58% and 3.8% correspondingly, which are satisfactorily low errors [38].…”
Section: Thermal Conductivitymentioning
confidence: 86%
See 3 more Smart Citations
“…The conventional thermal characterization procedure was compared with the experimental results. It was concluded that errors for the thermal conductivity and the specific heat capacity were 0.58% and 3.8% correspondingly, which are satisfactorily low errors [38].…”
Section: Thermal Conductivitymentioning
confidence: 86%
“…A new procedure to determine the thermal parameters of a pouch cell has been introduced [38]. Gradient heat flux sensors was used for the determination of the specific heat capacity and through-plane thermal conductivity.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…A procedure with local heat flux measurements has been proposed by Murashko et al [12], which was used to determine the thermal conductivity and specific heat capacity of a pouch cell. Similarly, the approach presented in this paper includes the simultaneous acquisition of local temperature and heat flux density.…”
Section: Introductionmentioning
confidence: 99%